2018
DOI: 10.1017/s175173111700132x
|View full text |Cite
|
Sign up to set email alerts
|

Milk replacers supplemented with either L-arginine or L-carnitine potentially improve muscle maturation of early reared low birth weight piglets from hyperprolific sows

Abstract: As a result of the selection for genotypes with greater sow prolificacy, litter size increased and, concomitantly, average litter birth weight and early postnatal survival rates of low birth weight (L-BtW) offspring decreased. This study compared the impact of l-carnitine (CAR) and l-arginine (ARG) supplemented with a milk replacer and fed to L-BtW piglets born from large litters from days 7 to 28 of age on growth performance, carcass composition, organ and Semitendinosus muscle (STM) development. A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…NEFA and urea levels were both lower at two weeks after weaning compared to immediately after the drenching period. Plausible explanations for these findings could be that neonatal piglets have a higher demand for fatty acid mobilization and gluconeogenesis in response to an increased energy demand, as suggested by Madsen et al [24], and the high amount of fats that can be found in the sow's milk [62]. Since this study showed no effect of drenching on the protein or lipid metabolism, nor any increase (or decrease) in glucose levels, and high (or low) blood glucose concentrations are correlated to the chance of survival [49], it can be assumed that drenching did not impose a significant threat on the pigs' survival chances.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…NEFA and urea levels were both lower at two weeks after weaning compared to immediately after the drenching period. Plausible explanations for these findings could be that neonatal piglets have a higher demand for fatty acid mobilization and gluconeogenesis in response to an increased energy demand, as suggested by Madsen et al [24], and the high amount of fats that can be found in the sow's milk [62]. Since this study showed no effect of drenching on the protein or lipid metabolism, nor any increase (or decrease) in glucose levels, and high (or low) blood glucose concentrations are correlated to the chance of survival [49], it can be assumed that drenching did not impose a significant threat on the pigs' survival chances.…”
Section: Discussionmentioning
confidence: 94%
“…In order for LBW piglets to acquire an adequate amount of energy and nutrients, farmers are often suggested to drench them with milk replacer, colostrum or enriched formula [21,23,24,37,38]. However, supplementing piglets via drenching implies chasing, picking up, restraining and drenching the animals while they are often agitated or scared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that even the control piglets received an amount of L‐carnitine via the milk replacer sufficient to facilitate all L‐carnitine‐dependent functions in intermediary metabolism under the assumption that endogenous L‐carnitine biosynthesis may be limited in low birth‐weight piglets. In another study of the same group with an identical experimental design but a slightly lower L‐carnitine dose (400 mg/piglet and day), L‐carnitine supplementation also failed to significantly improve growth performance, semitendinosus muscle weight and myofibre size of low birth‐weight piglets ( n = 30, female and castrated from Swiss Large White sows) reared with a mainly cow milk product‐based milk replacer from day 7 to 28 of age (Madsen, Mueller et al., ). It is likely that the same reason as in the study before (Madsen, Seoni et al., ) accounts for the lack of effect of supplemental L‐carnitine.…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 99%
“…Enzyme activity analysis in the semitendinosus muscle. To characterise the citric acid cycle activity, lipid oxidation and glycolytic capacity, activities of citrate synthase (CS; EC 4.1.3.7), β-hydroxyacyl-CoA dehydrogenase (HAD; EC 1.1.1.35) and lactate dehydrogenase (LDH; EC 1.1.1.27), respectively, were measured in the STM d and STM l as previously described by Madsen et al (25) . In brief, protein was extracted from 100 μg of muscle samples that were stored at −80°C.…”
Section: Histochemical Analysis Of the Semitendinosus Musclementioning
confidence: 99%